2018
DOI: 10.1590/s1980-6574201800010014
|View full text |Cite
|
Sign up to set email alerts
|

Acute melatonin administration enhances aerobic tolerance: an analysis of biochemical and hematological parameters

Abstract: This study is aimed at testing the acute melatonin administration (oral; 6 mg) on aerobic tolerance at cycloergometer and analyzing the consequences on biochemical and hematological parameters. Methods: The maximal aerobic capacity intensity (iMAC) at cycloergometer of eleven male healthy men (24.18±3.92 years-old; 87.07±12.48 kg; 1.82±0.05 m; 26.18±3.63 kg/m 2 ; and 16.28±5.77 % of fat) was individually determined and used to perform a time to exhaustion (tlim) trial of 30 minutes after melatonin or placebo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Moreover, morning (i.e., 07:30 a.m.) ingestion of MEL (5 mg) decreased only morning (i.e., 08:00 a.m.) short-term maximal performances but not performances achieved at 12:00 a.m. and 4:00 p.m. (20). However, more recent studies (8,12) have shown that MEL ingestion improved short-term and aerobic performances. In addition, another study in rats (9) found that MEL ameliorates aerobic performance during a swimming exercise until exhaustion.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, morning (i.e., 07:30 a.m.) ingestion of MEL (5 mg) decreased only morning (i.e., 08:00 a.m.) short-term maximal performances but not performances achieved at 12:00 a.m. and 4:00 p.m. (20). However, more recent studies (8,12) have shown that MEL ingestion improved short-term and aerobic performances. In addition, another study in rats (9) found that MEL ameliorates aerobic performance during a swimming exercise until exhaustion.…”
Section: Discussionmentioning
confidence: 88%
“…MEL has a protective effect on muscle and hepatic glycogen stores by inhibiting their depletion (23,31,37) and also it improves lipid metabolism (28). Furthermore, exogenous MEL ingestion has improved short-term and aerobic performances (8,12). From these observations, MEL seems a potential reasonable ergogenic aid with a considerable protective effect from muscle fatigue after intense exercise.…”
Section: Introductionmentioning
confidence: 99%
“… : 70%, 90%) Significantly increased MT level, TAC and GPx levels, decreased DNA damage in MT-treated group vs placebo group after 2-week exercise MT treatment strengthens antioxidant state of athletes and protects DNA from damage caused by high intensity exercise Ziaadini et al 2017 [ 118 ] Two groups of sedentary women: involved in exercise training and treated with MT ( n = 10) and only training ( n = 10), mean age: 24.2 ± 1.03 and 23.4 ± 1.83 years, respectively 3 mg/day MT supplementation before exercise training 8-week (3 days/week) exercise training of increasing intensity and volume from 60 to 80% HRmax through 15 to 45 min Significantly increased levels of MDA after long-lasting aerobic exercise training. Suppression of post-exercise increased MDA in the exercising and supplemented group Supplementation with MT may decrease ROS levels, thus improve lipid profile Beck et al 2018 [ 119 ] 11 males moderately active, mean age: 24.18 ± 3.92 years MT (6 mg) or placebo ingestion 30 min before exercise Exercise on cycloergometer with initial workloads of 75 W and increments of 15 W each 3 min till exhaustion Maximal aerobic capacity 120.88 ± 18.78 W A time to exhaustion significantly lower in placebo group compared to that with MT administered by approximately 19% MT supplementation enhanced aerobic tolerance but was without effect on the biochemical and hematological parameters Brandenberger et al 2018 [ 120 ] Ten cyclists long-distance training, mean age 25.0 ± 4.0 years 5 mg MT administered 15 min before time trial. Controls: placebo 15 min before time trial 32.2 km cycling time trial performance at 62.7 ± 6.8 (mL kg −1 min −1 ) on ergometer.…”
Section: Role Of Melatonin Supplementation In Response To Exercise-induced Oxidative Stressmentioning
confidence: 99%
“…The data indicate MT intake reduced the markers of OS and inflammation in athletes engaging in severe high-intensity exercise, independently of timing of MT intake. Only three [ 119 121 ] of 11 presented experimental studies examined the MT influence on redox status followed moderate-intensity exercise. These authors found no effect of the hormone (5–6 mg doses) on biochemical and hematological parameters.…”
Section: Role Of Melatonin Supplementation In Response To Exercise-induced Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation